Blogging to Write: Promoting Learner Independence in a 4.0 Learning Environment during the pandemic Covid-19 - Marleiny Radjuni (Hasanuddin University, 2022)
The goal of this action research project is to investigate how a blog writing project may help university students become autonomous language learners especially in the 4.0 learning environment.. This research also aims to determine the value of using a blog to help students improve their writing skills. Questionnaires and interviews were used to collect data at the end of the term. At this point, students were invited to consider their feeling and perceptions regarding the blog, as well as how it helped them practice writing outside of class, especially in the situation of pandemic Covid-19 nowadays. The study found that students' reported benefits of utilizing blogs included increased interest and motivation to use English as a result of interaction with, and feedback from, classmates and teachers. This can tell that they have already become autonomous learners. The preliminary findings also suggest that learners who participated in the blog project were interested in continuing to blog even after the semester finished. Further research needs to focus on whether or not learners did continue using this resource after the course ended.